Incidence and risk factors of suicide after a prostate cancer diagnosis: a meta-analysis of observational studies. Issue 4 (November 2018) - Guo, Zhenlang; Gan, Shu; Li, Yuan; Gu, Chiming; Xiang, Songtao; Zhou, Jianfu; Gong, Leiliang; Chan, Franky; Wang, Shusheng
Abstract Background Whether the diagnosis of prostate cancer is a contributory psychological stress that causes excess risk of suicide among affected men remains controversial. We performed a meta-analysis of previous studies to investigate suicide incidence and associated risk factors among men diagnosed with prostate cancer. Methods The MEDLINE, Embase, Cochrane Library, and PsycINFO databases were searched to identify eligible studies published before April 2018. The inverse variance method with random-effects modeling was used to calculate summary relative risks (RRs) and their associated 95% confidence intervals (CIs). Results Eight observational studies involving 1, 281, 393 men diagnosed with prostate cancer and 842, 294 matched prostate cancer-free men were included. An overall increased RR of suicide of 2.01 (95% CI: 1.52–2.64;P < 0.001;I 2 = 91.8%) was observed among men diagnosed with prostate cancer compared with those without prostate cancer during the first year, especially during the first 6 months (RR = 2.24, 95% CI: 1.77–2.85;P < 0.001;I 2 = 61.1%) after diagnosis. Moreover, prostate cancer patients were at an increased risk of suicide among men aged 75 years or older (RR = 1.51, 95% CI: 1.04–2.18;P = 0.028;I 2 = 91.5%) and treated with hormonal therapy (RR = 1.80, 95% CI: 1.54–2.12;P < 0.001;I 2 = 0%). Furthermore, marital status, race, disease risk category, and socioeconomic status were not associated with increased suicide risk in men with prostate cancer. Conclusions Current evidence indicates that the risk of suicide is increased among men diagnosed with prostate cancer, particularly those aged 75 years or older, <12 months after diagnosis, and treated with hormonal therapy. Healthcare providers should be aware of these special populations considered at high risk of suicide. Hence, further research should be conducted to refine suicide risk assessment with detection tools and to develop the best practices for prevention.